Modeling Document Summarization as Multi-objective Optimization - Lei Huang; Yanxiang He; Furu Wei; Wenjie Li (2010 Third International Symposium on Intelligent Information Technology and Security Informatics, 2010)
In this paper, we consider document summarization as a multi-objective optimization problem involving four objective functions, namely information coverage, significance, redundancy and text coherence. These functions measure the possible summaries based on the identified core terms and main topics (i.e. a cluster of semantically or statistically related core terms). We choose the DUC 2005 and 2006 query-oriented summarization tasks to exam the proposed model. The encouraging results indicate that the multi-objective optimization based framework for document summarization is truly a promising research direction.